2019
DOI: 10.3389/fmicb.2019.01272
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mode and Carbon Source Impact the Surfaceome Dynamics of Lactobacillus rhamnosus GG

Abstract: Bacterial biofilms have clear implications in disease and in food applications involving probiotics. Here, we show that switching the carbohydrate source from glucose to fructose increased the biofilm formation and the total surface-antigenicity of a well-known probiotic, Lactobacillus rhamnosus GG. Surfaceomes (all cell surface-associated proteins) of GG cells grown with glucose and fructose in planktonic and biofilm cultures were identified and compared, which indicated carbohydrate so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…These enzymes have been shown to protect Mtb against oxidative stress by the reduction of superoxide radicals into less toxic intermediates for inhibiting autophagy, apoptosis, and cellular damage ( 78 ). Iron-storing proteins ferritin (BfrB) and bacterioferritin (BfrA) can confer increased redox resistance to Mtb and protect the cells against oxidative stress and hypoxia, respectively ( 79 ). Here, these iron-storing proteins displayed biofilm subtype-specific abundance changes, implying that SBFs could rely on BfrB to cope with hypoxia and PBFs could rely on BrfA to help cells grow at the air-liquid interface.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes have been shown to protect Mtb against oxidative stress by the reduction of superoxide radicals into less toxic intermediates for inhibiting autophagy, apoptosis, and cellular damage ( 78 ). Iron-storing proteins ferritin (BfrB) and bacterioferritin (BfrA) can confer increased redox resistance to Mtb and protect the cells against oxidative stress and hypoxia, respectively ( 79 ). Here, these iron-storing proteins displayed biofilm subtype-specific abundance changes, implying that SBFs could rely on BfrB to cope with hypoxia and PBFs could rely on BrfA to help cells grow at the air-liquid interface.…”
Section: Discussionmentioning
confidence: 99%
“…In many bacteria, the (p)ppGpp levels are regulated by an alarmone synthetase/hydrolase Rel in response to amino acid starvation, in which the branched-chain amino acids, such as valine and isoleucine, play an important role [78]. Previously, we demonstrated that in Lactobacillus rhamnosus, the surface-associated aminopeptidases (PepN/PepC) degrade oligopeptides while bound to the biofilm matrix, indicating that the cytoplasmic enzymes can also confer a similar function at the cell surface [79]. While the peptidolytic enzymes were less abundant on biofilm cells, an oligopeptide transporter protein, OppA, was notably more strongly produced on fully mature biofilm cells (SDBF_24 h) compared to planktonic cells or biofilm cells derived from exponential-phase cells (EDBF_24 h).…”
Section: Peptidolytic Moonlighters and Tolerancementioning
confidence: 99%
“…Before protein identification, biofilm viability with and without the trypsin treatment was first assessed to exclude possible effects of trypsin on biofilm integrity. Biofilms were grown on G coupons in 12-WPs and then transferred into Falcon tubes (50 mL) containing 1 mL of 100 mM acetate buffer (pH 4.7), a condition preventing the release of the adhesive moonlighting proteins [56]. The tubes were sonicated (25 • C, 35 kHz, 5 min) and detached bacterial cells were collected by centrifugation (4 • C, 4000× g, 2 min).…”
Section: Trypsin Shaving Of Matrix-associated Proteinsmentioning
confidence: 99%